Deficiency of heme-regulated eIF2α kinase decreases hepcidin expression and splenic iron in HFE−/− mice - Sijin Liu; Rajasekhar N.V.S. Suragani; Anping Han; Wanting Zhao; Nancy C. Andrews; Jane-Jane Chen (Haematologica, 2008)
Heme-regulated eIF2α kinase (HRI) is essential for regulating globin translation in iron deficiency and in β-thalassemia. We investigated the role of heme-regulated eIF2α kinase in hemoglobin and red blood cell production as well as in iron homeostasis in a mouse model of iron overload. We show that HRI deficiency does not significantly affect red cell parameters of hemochromatosis (HFE−/−) mice. Importantly, heme-regulated eIF2α kinase deficiency exacerbates decreases in hepcidin expression and splenic macrophage iron in HFE−/− mice. Furthermore, the serum level of bone morphogenic protein 2, which positively regulates hepcidin, is reduced in heme-regulated eIF2α kinase deficiency, but not in HFE deficiency.